The Relationship Between Mother's Level of Knowledge and Giving MP-ASI (Weaning Food) on Babies Under 6 Months - Putri Kusuma Wardani; Yessy Nur Endah Sary; Tutik Hidayati (Health and Technology Journal (HTechJ), 2023)
Giving weaning food (MP-ASI) too early has many impacts on the health of babies, including diarrheal diseases. This is because the baby's digestive system is not ready to accept food other than breast milk, causing a reaction in the digestive system. This study aimed to analyze the relationship between a mother's level of knowledge and giving MP-ASI (weaning food) on babies under 6 months. This study uses an analytic design observational with an approach Cross-sectional. Data were taken from interviews and questionnaire sheets at Posyandu Kenanga Desa Labruk Lor, held in November 2022 with a total population of 32 mothers with babies aged 0-6 months and a sample of 32 respondents using the technique of total sampling. Data collection includes coding, editing, and tabulating. Bivariate analysis using uji Chi-Square shows p-value= 0.001 < α 0.05 means a relationship exists between the mother's knowledge level and the provision of MP ASI to infants under six months old. A correlation value of 0.543 means that the mother's level of knowledge has a strong relationship with the provision of MP ASI to infants under 6 months old. The conclusion of the study, there is a relationship between the level of mother's knowledge and the provision of MP-ASI to infants under six months at Posyandu Kenanga Desa Labruk Lor in 2022. The suggestions are that research sites should conduct counseling activities related to exclusive breastfeeding and MP-ASI provision to increase mothers' knowledge.